Relationship of blood monocytes with chronic lymphocytic leukemia aggressiveness and outcomes: a multi‐institutional study. Issue 7 (24th April 2016) - Friedman, Daphne R.; Sibley, Alexander B.; Owzar, Kouros; Chaffee, Kari G.; Slager, Susan; Kay, Neil E.; Hanson, Curtis A.; Ding, Wei; Shanafelt, Tait D.; Weinberg, J. Brice; Wilcox, Ryan A.
Abstract : Monocyte‐derived cells, constituents of the cancer microenvironment, support chronic lymphocytic leukemia (CLL) cell survival in vitro via direct cell‐cell interaction and secreted factors. We hypothesized that circulating absolute monocyte count (AMC) reflects the monocyte‐derived cells in the microenvironment, and that higher AMC is associated with increased CLL cell survival in vivo and thus inferior CLL patient outcomes. We assessed the extent to which AMC at diagnosis of CLL is correlated with clinical outcomes, and whether this information adds to currently used prognostic markers. We evaluated AMC, clinically used prognostic markers, and time to event data from 1, 168 CLL patients followed at the Mayo Clinic, the Duke University Medical Center, and the Durham VA Medical Center. Elevated AMC was significantly associated with inferior clinical outcomes, including time to first therapy (TTT) and overall survival (OS). AMC combined with established clinical and molecular prognostic markers significantly improved risk‐stratification of CLL patients for TTT. As an elevated AMC at diagnosis is associated with accelerated disease progression, and monocyte‐derived cells in the CLL microenvironment promote CLL cell survival and proliferation, these findings suggest that monocytes and monocyte‐derived cells are rational therapeutic targets in CLL. Am. J. Hematol. 91:687–691, 2016. © 2016 Wiley Periodicals, Inc.